2015
DOI: 10.1093/cercor/bhv179
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Ventral and Dorsal Streams for Conceptual and Production-Related Components of Tool Use in Acute Stroke Patients

Abstract: Impaired tool use despite preserved basic motor functions occurs after stroke in the context of apraxia, a cognitive motor disorder. To elucidate the neuroanatomical underpinnings of different tool use deficits, prospective behavioral assessments of 136 acute left-hemisphere stroke patients were combined with lesion delineation on magnetic resonance imaging (MRI) images for voxel-based lesion-symptom mapping. Deficits affecting both the selection of the appropriate recipient for a given tool (ToolSelect, e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 134 publications
6
48
0
4
Order By: Relevance
“…Another possibility is that the pantomime is subserved by a widely distributed network in the left hemisphere, including premotor and parietal cortices together with 15 connecting fiber tracts, which could not be analyzed by MVPA. More recent studies with a larger sample of acute stroke patients showed that the IPL is responsible for pantomime integrity (Hoeren et al 2014;Martin et al 2015;Martin et al 2016), which is in accordance with the present finding.…”
Section: Iplsupporting
confidence: 92%
“…Another possibility is that the pantomime is subserved by a widely distributed network in the left hemisphere, including premotor and parietal cortices together with 15 connecting fiber tracts, which could not be analyzed by MVPA. More recent studies with a larger sample of acute stroke patients showed that the IPL is responsible for pantomime integrity (Hoeren et al 2014;Martin et al 2015;Martin et al 2016), which is in accordance with the present finding.…”
Section: Iplsupporting
confidence: 92%
“…Other studies reported the involvement of the left ventral premotor cortex (Chao & Martin, ; Grafton, Fadiga, Arbib, & Rizzolatti, ; Kroliczak & Frey, ), the left inferior frontal gyrus (IFG) bordering pars opercularis (e.g., see Johnson‐Frey et al, ), and the left insula (Brandi et al, ) when participants viewed tool images or were instructed to process the appropriate manner with which to grasp or manipulate objects. Neuropsychological evidence consistent with those fMRI findings suggests that lesions to the left IFG and adjacent structures in the insula impair the ability to select the appropriate manner with which to grasp or use an object (e.g., see Watson & Buxbaum, ; see also Goldenberg, Hermsdorfer, Glindemann, Rorden, & Karnath, ; Martin et al, ).…”
Section: Introductionmentioning
confidence: 68%
“…However, the lesions associated with gesture deficits included lesions associated with imitation deficits, including slightly ventral areas (orbital part of the IFG and temporal pole of the superior temporal gyrus). Imitation is possible with simple visual-motor conversion, whereas gesture from verbal instruction requires semantic processing, and the ventral regions are more involved (100, 117). The current findings were consistent with the results of these previous studies and showed that the visuo-motor conversion region and semantic processing region overlap, but do not completely match.…”
Section: Discussionmentioning
confidence: 99%